Misleading online advertising in the new business era in India - Pongiannan, K; Viswanathan, P (Asian Journal of Interdisciplinary Research, 2018)
One of the most substantive developments in the delivery of marketing activities over the last few years has definitely been the coming into view and growth of Internet shopping. This compared to other things new form of communication has totally changed and improved the buying and selling of products and services, enabling customers to select and import items - many of which are not available through local shop fronts - directly from vendors around the world with the click of a button, and often at a reduced price. Although online shopping has given a new international landscape to conduct business and the use of this medium and the absence of face-to-face interactions have presented the law with many challenges in terms of the scope of consumer protection. This article examines the nature and extent of sneaky and false and dishonest online advertising and looks at the degree to which common law and laws and law making have changed to deal with false, dishonest or sneaky and false advertising on the Internet.